2014
DOI: 10.1111/papr.12225
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction with Fentanyl Sublingual Spray in Opioid‐Tolerant Patients with Breakthrough Cancer Pain

Abstract: These data indicate markedly improved satisfaction among patients receiving fentanyl sublingual spray relative to previous BTCP medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
(27 reference statements)
0
6
0
1
Order By: Relevance
“…A total of 130 patients were enrolled in the study (Table ) . and 98 (75.4%) patients completed the open‐label titration phase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 130 patients were enrolled in the study (Table ) . and 98 (75.4%) patients completed the open‐label titration phase.…”
Section: Resultsmentioning
confidence: 99%
“…and 98 (75.4%) patients completed the open‐label titration phase. Thirty‐two patients (24.6%) discontinued participating in the study due to either an inability to determine a successful dose ( n = 3; 2.3%), intercurrent illness or surgery ( n = 1; 0.8%), an AE ( n = 6; 4.6%), a protocol violation ( n = 2; 1.5%), an investigator ( n = 2; 1.5%), patient decision ( n = 15; 11.5%), or other reason ( n = 3; 2.3%) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the findings in Rauck et al, fentanyl sublingual spray measured an increase in TSQM score from baseline to end of titration in all four domains. 36 However, it should be noted that the retrospective design of this analysis may have introduced recall bias. Some studies have shown that patients have a preference for transmucosal or sublingual routes of administration.…”
Section: Patient Acceptability and Preferencementioning
confidence: 99%
“…As well, a fentanyl sublingual spray formulation administered for BTCP has been shown to be efficacious and well tolerated [20][21][22][23] and produce a significantly greater reduction in pain intensity versus placebo as early as 5 min after dosing, with a duration of 60 min (the last time interval assessed) [20]. A sublingual administration route may provide more rapid onset of action versus other BTCP treatment routes of administration because of the high permeability and more available blood supply to the sublingual cavity relative to the oral route [24].…”
Section: Practice Pointsmentioning
confidence: 99%